PENINGKATAN KUALITAS PENGAJAR BAHASA ARAB SEBAGAI UPAYA MENINGKATKAN STANDAR MUTU PEMBELAJARAN BAHASA ARAB - Abdul Wahab Rosyidi (Jurnal Ilmiah Peuradeun, 2014)
In reality, the objectives, methods, 'and materials of teaching and learning Arabic have not improved the Arabic students' achievements. One of the causes is the unqualified teachers', they do not have enough knowledge of applied linguistic theories, the principles, approches, and methods of language learning, and material improvement. While, teachers' have important roles in Arabic learning process. The success of Arabic learning results from, among other things, the teachers' abilities that inclued "al Janib al Lughawy, al Janib al Tsaqafy, al Janib al Mihny". Therefore, improving the Arabic teachers quality is one of the alternatives to enhance the quality standard of Arabic learning.